ПУТИ ОПТИМИЗАЦИИ ОЦЕНКИ ФОРМИРОВАНИЯ ПРАКТИЧЕСКИХ НАВЫКОВ У ОБУЧАЮЩИХСЯ - Аль-Харес, Милад Мтанусович; Прудникова, Мария Дмитриевна; Кириченко, Инга Якубовна; Панкратова, Полина Андреевна; Лисовская, Евгения Олеговна; Гавщук, Ольга Владимировна (FORCIPE, 2022)